American Indian biographies - Markowitz, Harvey; Barrett, Carole A. (Pasadena, Calif. : Salem Press, 2005)
Contains biographical sketches, ranging in length from 300 to 3,000 words, on figures in North American Indian history, extending from the arrival of European colonists on North American shores to the early twenty-first century.
Reifel, Ben -- Renville, Joseph -- Ridge, John Rollin -- Ridge, Major -- Riel, Louis, Jr. -- Riggs, Lynn -- Robertson, Robbie -- Rocky Boy -- Rogers, Will -- Roman Nose -- Ross, John -- Ross, Mary G.-- Sacagawea -- Sainte-Marie, Buffy -- Samoset -- Sampson, Will -- Sassacus -- Satank -- Satanta -- Scarface Charlie -- Scholder, Fritz -- Seattle -- Sequoyah -- Shábona -- Shikellamy -- Short Bull -- Silko, Leslie Marmon -- Silverheels, Jay -- Sitting Bull -- Slocum, John -- Smohalla -- Snake, euben -- Spotted Tail -- Spybuck, Ernest -- Squanto -- Standing Bear -- Standing Bear, Luther -- Studi, Wes -- Stumbling Bear -- Sweezy, Carl -- Swimmer -- Sword, George -- Tall Bull -- Tallchief, Maria -- Tammany -- Tapahonso, Luci -- Tarhe -- Tavibo -- Tawaquaptewa -- Tecumseh -- Teedyuscung -- Tekakwitha, Kateri -- Ten Bears -- Tendoy -- Tenskwatawa -- Thorpe, Jim -- Tiger, Jerome R. -- Tomah -- Tomochichi -- Trudell, John -- Tsali -- Tsatoke, Monroe -- Two Crows -- Two Leggings -- Two Moon -- Two Strike -- Tyon, Thomas -- Uncas -- Victorio -- Vizenor, Gerald R[obert] -- Waban -- Waheenee -- Wapasha -- Ward, Nancy -- Warren, William W. -- Warrior, Clyde -- Washakie -- Watie, Stand -- Wauneka, Annie Dodge -- Weatherford, William -- Weetamoo -- Welch, James -- White Bird -- White Bull -- White Cloud -- White Eyes -- White Hat, Albert -- White Man Runs Him -- Wildcat -- Williams, Eleazar -- Winema -- Winnemucca, Sarah -- Wooden Leg -- Wovoka -- Wright, Allen -- Yellow Wolf -- Yellow Tail, Robert -- Yonaguska -- Young Bear -- Young Man Afraid of His Horses -- Zotom -- Time Line -- Tribal Affiliations Index -- Index.
Essays originally appeared in American Indian biographies (1999), Dictionary of world biography, Great lives from history: the Renaissance & early modern era, 1454-1600 (2005), and American ethnic writers (2000). New material has been added.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Indians of North America -- Biography; Indians of North America -- Kings and rulers -- Biography; Indian women -- North America -- Biography; Indian authors -- North America -- Biography; Native peoples -- Biography; Native peoples -- Kings and rulers -- Biography; Native women -- North America -- Biography; Peuples autochtones -- Amérique du Nord -- Biographies; Peuples autochtones -- Amérique du Nord -- Rois et souverains -- Biographies; Femmes des Peuples autochtones -- Amérique du Nord -- Biographies; Écrivains des Peuples autochtones -- Amérique du Nord -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; BIOGRAPHY & AUTOBIOGRAPHY -- Native Americans; Indian authors; Indian women; Indians of North America; Indians of North America -- Kings and rulers; North America; Biographies; Biographies; Biographies